Preparation of calcium oxide/graphitic carbon nitrides (CaO/g-C3N4) composite for photocatalyst dye degradation - Chinanun Chaisrisongkram; Thutiyaporn Thiwawong; Korakot Onlaor; Benchapol Tunhoo (My University, 2024)
Dye degradation properties of composited calcium oxide (CaO) and graphitic carbon nitride (g-C 3 N 4 ) were studied.The CaO and g-C 3 N 4 nanoparticles were derived under separate thermal calcination processes from eggshells and melamine, respectively.Physical properties of the synthesized CaO and g-C 3 N 4 were investigated by X-ray diffractometry (XRD), Fourier-transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM).The synthesized CaO and g-C 3 N 4 nanoparticles were, then, composited at various concentrations, and the photocatalytic behaviors of the composited samples were investigated in an aqueous solution of methylene blue, with a irradiation source of 220 W white light-emitting diode lamp.Results showed that the optimal ratio of the composite material for dye degradation was 10% CaO:90% g-C 3 N 4 , giving 95.89% degradation efficiency with an exposure time of 15 min and degradation rate of 0.1727 min -1 .
Keywords: Graphitic carbon nitride; Degradation; Methylene blue; Advanced Photocatalysis Techniques